1985
DOI: 10.1042/bj2280227
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative aspects of mucus glycoprotein biosynthesis in rat gastric mucosa

Abstract: The synthesis of the polypeptide backbone of mucus glycoproteins in rat stomach was studied. CsCl centrifugation of the homogenate of [3H]serine pulse-chase labelled stomach or mucosal scrapings showed that [3H]serine was mainly incorporated into molecules having a density identical to that of proteins and that only 8-12% was incorporated into macromolecules with the density of mucus glycoproteins. [3H]-Galactose, however, was almost exclusively incorporated into macromolecules with a density identical to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In rats, it was found that sucraseisomaltase and maltase account for approximately 1% of mucosa proteins. 52 Total glycoprotein synthesis was found to be responsible for 6%-10% of total tracer incorporation in the mucosa, 53 whereas in rat liver about 10% of all proteins show a rapid turnover in the above range. 37,41 Our calculation of a size of 4% for such a rapidly turning over protein pool in human postoperative ileal mucosa would be in the range of these estimates and would, therefore, also support the validity of the rapidly turning over pool concept for explaining the enrichment changes that were seen during continuous isotope infusion over prolonged periods of time in ileal mucosa from controls.…”
Section: Resultsmentioning
confidence: 99%
“…In rats, it was found that sucraseisomaltase and maltase account for approximately 1% of mucosa proteins. 52 Total glycoprotein synthesis was found to be responsible for 6%-10% of total tracer incorporation in the mucosa, 53 whereas in rat liver about 10% of all proteins show a rapid turnover in the above range. 37,41 Our calculation of a size of 4% for such a rapidly turning over protein pool in human postoperative ileal mucosa would be in the range of these estimates and would, therefore, also support the validity of the rapidly turning over pool concept for explaining the enrichment changes that were seen during continuous isotope infusion over prolonged periods of time in ileal mucosa from controls.…”
Section: Resultsmentioning
confidence: 99%
“…According to animal data, this rapidly turning over protein pool in the gut mainly consists of enzymes or epithelial glycoproteins such as lactosaminoglycans or proteoglycans, which were found to have turnover rates in the range of 20%-30%/hour, depending on the physiologic conditions. 18 -22 Nevertheless, because the size of this specific pool amounts to Ͻ10% of the total protein pool, [23][24][25] the vast majority of proteins can still be studied in tracer infusion experiments such as ours.…”
Section: July-august 2005mentioning
confidence: 99%
“…18 -22 Nevertheless, because the size of this specific pool amounts to Ͻ10% of the total protein pool, [23][24][25] the vast majority of proteins can still be studied in tracer infusion experiments such as ours.…”
Section: July-august 2005mentioning
confidence: 99%
“…Practical problems of studies of the structure, function and metabolism of mucous secretions have been reviewed, and lack of knowledge about the biosynthesis of the core protein of mucus, and also controversy in the understanding of the mechanism of mucus secretion, were emphasized (Carlstedt et al, 1985). Since the early work of Kent & Allen (1968), biosynthesis of gastric mucus has been investigated by a number of laboratories (Dekanski et al, 1975;Jentjens et al, 1984;Jentjens & Strous, 1985;Kent, 1972;Lukie & Forstner, 1972;Parke & Symons, 1977;Snary & Allen, 1971, 1972Spohn & McColl, 1980, 1986Starkey et al, 1974;Trotman & Greenwell, 1979;Yeomans & Millar, 1980), but so far the mechanisms involved and the fractors controlling them remain obscure. Moreover, information about the biosynthesis and secretion of mucus by human gastric mucosa is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, information about the biosynthesis and secretion of mucus by human gastric mucosa is scarce. Jentjens & Strous (1985) have formulated a hypothesis which states that the backbone polypeptide of mucus only accounts for a small part of protein synthesis of mucus-producing cells. Our evidence, based on investigations of synthesis of proteins in vitro by intact gastric mucosa and by isolated gastric epithelial-cell preparations from the guinea pig (Spohn & McColl, 1980, 1986, as also by fresh human gastric mucosa, conflicts with this hypothesis, but suggests an alternative explanation for the findings.…”
Section: Introductionmentioning
confidence: 99%